Strategi Komunikasi dalam Tindak Tutur Pelayanan Publik di Kelurahan Tanah Garam Kota Solok - Wirasty. B, Rini; Marta, Redo Andi; Rahayu, Zona Rida; Halid, Elan; Putri, Mega (ASOSIASI IDEBAHASA KEPRI, 2024)
Good public service is the main responsibility in managing government and meeting all the needs of the community so that the services provided by government officials can be more satisfying to the community, a mindset change is needed from all government officials implementing public services as a first step in providing excellent service. because service is an activity carried out with full awareness and noble intentions to help others and provide the best to others as part of an effort to make himself and the institutions he manages become good in the eyes of the people served so as to create satisfaction.